Design, synthesis and biological evaluation of novel azaspiro analogs of linezolid as antibacterial and antitubercular agents - Gadekar, Pradip K.; Roychowdhury, Abhijit; Kharkar, Prashant S.; Khedkar, Vijay M.; Arkile, Manisha A.; Manek, Hardik; Sarkar, Dhiman; Sharma, Rajiv; Vijayakumar, V.; Sarveswari, S. (European Journal of Medicinal Chemistry, 2016)
The design, synthesis and antimicrobial evaluation of a novel series of azaspiro analogues of linezolid (1) have been described. Linezolid comprises of a morpholine ring which is known for its metabolism related liabilities. Therefore, the key modification made in the linezolid structure was the replacement of morpholine moiety with its bioisostere, 2-oxa-6-azaspiro[3.3]heptane. Furthermore, the replacement of N-acetyl terminal of 1 with various aromatic or aliphatic functionalities was carried out. The title compounds were evaluated against a panel of Gram-positive and Gram-negative bacteria and Mycobacterium tuberculosis. Subsequent structure-activity relationship (SAR) studies identified several compounds with mixed antibacterial and antitubercular profiles. Compound 22 (IC50 0.72, 0.51, 0.88, 0.49 mu g/mL for Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus subtilis, respectively) exhibited similar antibacterial profile as I. The N-acetyl derivative 18 was similar to 1 in antitubercular profile. Thus, the present study successfully demonstrated the use of azaspiro substructure in the medicinal chemistry of antibacterial and antitubercular agents. (C) 2016 Elsevier Masson SAS. All rights reserved.

Design, synthesis and biological evaluation of (E)-5-styryl-1,2,4-oxadiazoles as anti-tubercular agents - Upare, Abhay Atmaram; Gadekar, Pradip K.; Sivaramakrishnan, H.; Naik, Nishigandha; Khedkar, Vijay M.; Sarkar, Dhiman; Choudhari, Amit; Roopan, S. Mohana (Bioorganic Chemistry, 2019)
Cinnamic acid and its derivatives are known for anti-tubercular activity. The present study reports the synthesis of cinnamic acid derivatives via bioisosteric replacement of terminal carboxylic acid with ``oxadiazole''. A series of cinnamic acid derivatives (styryl oxadiazoles) were designed and synthesized in good yields by reaction of substituted cinnamic acids (2, 15a-15s) with amidoximes. The synthesized styryl oxadiazoles were evaluated in vitro for anti-tubercular activity against Mycobacterium tuberculosis (Mtb) H37Ra strain. The structure-activity relationship (SAR) study has identified several compounds with mixed anti-tubercular profiles. The compound 32 displayed potent anti-tubercular activity (IC50= 0.045 mu g/mL). Molecular docking studies on mycobacterial enoyl-ACP reductase enzyme corroborated well with the experimental findings providing a platform for structure based hit-to-lead development.
Keywords: 1; 2; 4-Oxadiazole; Anti-tubercular; Bioisosteres; Cinnamic acid; Molecular docking